Patterns of emergency admission for IBD patients over the last 10 years in Lothian, Scotland: a retrospective prevalent cohort analysis. Issue 1 (17th March 2022) - Lyons, Mathew; Derikx, Lauranne A. A. P.; Fulforth, James; McCall, Sophie; Plevris, Nikolas; Jenkinson, Philip W.; Kirkwood, Kathryn; Siakavellas, Spyros; Lucaciu, Laura; Constantine‐Cooke, Nathan; Arnott, Ian D.; Henderson, Paul; et al.
Summary: Objective: It is unclear how the compounding prevalence of inflammatory bowel disease (IBD) has translated into the causes and rates of hospitalisation, particularly in an era of increased biologic prescribing. We aimed to analyse these trends in a population‐based IBD cohort over the last 10 years. Design: The Lothian IBD registry is a complete, validated, prevalent database of IBD patients in NHS Lothian, Scotland. ICD‐10 coding of hospital discharge letters from all IBD patient admissions to secondary care between 1 January 2010 and 31 December 2019 was interrogated for admission cause, with linkage to local/national data sets on death and prescribed drugs. Results: Fifty‐seven per cent (4673/8211) of all IBD patients were admitted to secondary care for >24 h between 1 January 2010 and 31 December 2019. In patients <40 years, IBD was the commonest reason for admission (38% of admissions), whereas infection was the most common cause in those >60 years (19% of admissions). Three per cent (243/8211) of IBD patients accounted for 50% of the total IBD bed‐days over the study period. Age‐standardised IBD admission rates fell from 39.4 to 25.5 admissions per 100, 000 population between 2010 and 2019, an average annual percentage reduction of 3% (95% CI −4.5% to −2.1%, p < 0.0001). Non‐IBD admission rates were unchanged overall (145–137 per 100, 000 population) and specifically for serious (hospitalisation) and severe (ITU admission or death) infection over the same period. Conclusion: Despite compounding prevalence and increased biologic use, IBD admission rates are falling. The cause of admission varies with age, with infection the predominant cause in older patients. Abstract : Patterns of emergency admission for IBD patients over the last 10 years in Lothian, Scotland: A retrospective prevalent cohort analysis.